Impact of print bed build location on the dimensional accuracy and surface quality of parts printed by multi jet fusion - Sagbas, Binnur; Gumus, Beril Eker; Kahraman, Yusuf; Dowling, Denis P. (ELSEVIER SCI LTD, 2021)
Multi Jet Fusion (MJF) is one of the newly developed additive manufacturing techniques, based on the use of powder bed fusion technology. It provides the opportunity to build up 3D, complex polymer geometries, without the need for support structures. This study evaluates the effect of build location across a 380 x 284 mm(2) build plate, on both the dimensional accuracy and surface quality of polyamide 12 (PA12) parts printed using the MJF technique. The cube test samples were printed at each of the four corners and the center of the build plate. Dimensional deviations were determined using optical metrology measurements, while surface deviations were measured using 2D tactile and 3D optical profilometers. The density and the degree of crystallinity of the samples were determined using the Archimedes method and Differential Scanning Calorimetry analysis, respectively. Moreover, the morphology of the internal polymer surfaces was evaluated using Scanning Electron Microscopy. It was concluded that while overall printed part dimensions and crystallinity homogeneity were relatively uniform across the build plate, some variations were observed. Parts printed in particular, closer to the front of the build plate exhibited higher porosity, higher surface roughness along with the highest level of geometry deviation, compared with the CAD drawing. This is likely to be associated with some non-uniformities in heating and cooling of the PA12 polymer parts across the build plate.
Keywords: Additive manufacturing; Multi jet fusion; PA12; Powder bed fusion; Dimensional accuracy; Engineering